Interface‐Engineered Plasmonics in Metal/Semiconductor Heterostructures. Issue 17 (3rd June 2016) - Jia, Chuancheng; Li, Xinxi; Xin, Na; Gong, Yao; Guan, Jianxin; Meng, Linan; Meng, Sheng; Guo, Xuefeng
Abstract : Plasmonic manipulation of light in metal/semiconductor heterostructures is a powerful tool that exploits extraordinary optical properties of metallic nanostructures to concentrate and control light at the nanometer scale. Here, recent progresses in the mechanism and strategies developed for the control of plasmon‐induced optical field distribution, hot electron injection and energy transfer at the metal/semiconductor heterostructure interface are discussed. This is of crucial importance to the selection of matched materials, the design of optimized device architectures and the future development of efficient fabrication technologies for plasmon‐enhanced photocatalytic and photovoltaic applications. Abstract : Recent progresses in the mechanism and strategies developed for controlling plasmon‐induced optical field distribution, hot electron injection and energy transfer at the metal/semiconductor heterostructure interface are reviewed. This is of crucial importance to the selection of matched materials, the design of optimized device architectures and the future development of efficient fabrication technologies for plasmon‐enhanced photocatalytic and photovoltaic applications.